IDENTIFIKASI CEMARAN Escherichia coli DAN FAKTOR PENCEMAR PADA DAGING AYAM DI PASAR KETAPIAN DENPASAR TIMUR - Putu Indah Arta Pratiwi; Gusti Ayu Made Ratih Kusuma Ratna Dewi; I Gede Sudarmanto (Jurnal Kesehatan Lingkungan (JKL), 2022)
Chicken meat has high protein and easily to be found in traditional markets. Chicken meat can be contamination by bacteria, especially by Escherichia coli. This research was to identify Escherichia coli contamination and contamination factors on chicken meat in East Denpasar Ketapian market. This research used a descriptive method with probability sampling technique, namely simple random sampling. Total samples used were 12 samples of chicken meat. The results show 6 samples (50 %) were positively contaminated by Escherichia coli. Contamination factors cause by environmental factors (garbage with heaped conditions, trash in open conditions, water not flow), equipment hygiene (not clean knives), and personal hygiene factors (sellers not clean their hands or use gloves and wear aprons in dirty conditions). Conclusion, 50 % of chicken meat samples from East Denpasar Ketapian market were contaminated by Escherichia coli and contamination factors that can affect are environmental factor, equipment hygiene and personal hygiene.